Evaluation of Naproxen and Ibuprofen efficacy on post maxillomandibular fixation trismus - Bara S Minwah; Mohmmed K Hassouni (University of Mosul, College of Dentistry, 2011)
Aims of the study: The study aims to evaluate the effect of naproxen and ibuprofen on post maxillo-mandibular fixation (MMF) limited mouth opening. Materials and Methods: The study was per-formed at AL-Jumhoori Teaching Hospital in Mosul City on 30 patients with mandibular fracture and or maxilla who were treated with MMF. The medicaments were allocated to 30 patients using a double blind randomization study who were divided into three groups .Group 1(10 patients) received Ibuprofen. Group 2(10 patients) received Naproxen and Group 3 (10 patients) received placebo . Immediately after MMF release, the maximum mouth opening was measured as the inte-rincisal distance be-tween the right upper central incisor and the right lower central incisor. After one hour ,the inter-incisal distance was measured again and recorded .The data were analyzed using paired T-test and Duncan multiple analysis. Results: Both Naproxen and Ibuprofen have a statistically significant effect on the improvement of post-MMF limited mouth opening compared to placebo . At the same time there was no significant difference between the effect of Naproxen and that of Ibuprofen on the improvement of post MMF-limited mouth opening .The study also showed that there is inverse correlation between the MMF period and the maximum mouth opening immediately after MMF release. Conclusions: There is no significant difference between the effect of naproxen and that of ibuprofen on the improvement of limited mouth opening after MMF release. The available and cheaper drugs can be prescribed.